Registration ; Warlordism ; Going with the wind [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Looks at 1992 registration of voters and the chaos. Investigate the alledge "warlords" that manipulates local politics. Focuses Ali Dimaporo, Mindanao's well known politician. Looks at windsurfers in Lake Caliraya.
Registration (12 min.) -- Warlordism (15 min.) -- Going with the wind (6 min.)
VHS.
Keywords: Elections -- 1992. -- Philippines; Voting -- 1992. -- Philippines; Political parties -- 1992. -- Philippines; Windsurfing -- Philippines -- Caliraya (Laguna); Lanao del Sur -- Politics and government